Intravenous Epoprostenol for Management of Pulmonary Arterial Hypertension during Pregnancy - Timofeev, Julia; Ruiz, George; Fries, Melissa; Driggers, Rita W. (American Journal of Perinatology Reports, 2013)
Background Pulmonary arterial hypertension carries a high risk of mortality in pregnancy. Recent advances in treatment may improve disease course and allow for successful management of the pregnancy.Case Report We present the case of a 20-year-old gravida 1, para 0 with diagnosis of severe primary pulmonary hypertension. The patient was managed with epoprostenol (prostacyclin) infusion via an indwelling catheter, which was initiated at 23 weeks' gestation. The dose was adjusted to the patient's symptoms and a successful vaginal delivery was achieved at 36 weeks' gestation. Although maternal postpartum course was uncomplicated, unexplained neonatal demise occurred at 11 days of life.Conclusion Successful management of pulmonary hypertension in pregnancy can be accomplished with a multidisciplinary approach and intensive therapy. Long-term effects of epoprostenol on fetal or neonatal well-being are unknown.
Keywords: epoprostenol; pulmonary hypertension; prostaglandin; prostacyclin